Da'wah Communication Strategies in Dealing with Online Gambling among Teenagers - M. Nashoihul Ibad; Dito Anurogo; Novianto Puji Rahardjo (PT Agung Media Publisher, 2024)
Online gambling has become a serious problem that threatens the younger generation, especially teenagers.